Features of the formative educational training groups in Youth sports schools in terms of our time - Artem Zhytnitskyi (Kharkiv State Academy of Physical Culture, 2015)
Purpose: identify the factors affecting the effective performance of the Children and Youth Sports School at the initial and preliminary stage of basic training. Material and Methods: analysis of the literary base, pedagogical research methods, statistical methods, questionnaire. Results: the understanding of the factors influencing the motor skills formation of students is displayed. The author grounded three-dimensional understanding of dissimilar conditions and factors determining the functionality of a Children and Youth Sports School taking into account the motivation of students the scope of use of the skills and other factors which don't deal with teaching science. Conclusions: it was found that miscellaneous factors, many of which are associated with the state of material and technical base and infrastructure of the school, the region and the country as a whole affect screening the contingent of a Children and Youth Sports School